2020
DOI: 10.1111/1471-0528.16285
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric admissions to intensive care units in Australia and New Zealand: a registry‐based cohort study

Abstract: Objective Describe the epidemiology of obstetric patients admitted to an Intensive Care Unit (ICU). Design Registry-based cohort study. Setting One hundred and eighty-three ICUs in Australia and New Zealand. Population Women aged 15-49 years, admitted to ICU between 2008 and 2017, classified as pregnant, postpartum or with an obstetric-related diagnosis. Methods Data were extracted from the Australia and New Zealand Intensive Care Society (ANZICS) Adult Patient Database and national agencies. Main outcome meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 23 publications
0
27
1
Order By: Relevance
“…The occurrence of obstetric admission to ICU in the present study was much higher (4.1%) considering the total number of deliveries in the two maternity hospitals than that reported in developed countries or even in developing countries. A study conducted in Australia and New Zealand found an annual average of 1.3% of ICU admissions (Alkema et al , 2016; Maiden et al , 2020), and the frequency in India was 0.5% (Vargas et al , 2019). The results were also higher than the WHO estimate for pregnant Brazilians requiring ICU admission (2.1%) (Souza et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of obstetric admission to ICU in the present study was much higher (4.1%) considering the total number of deliveries in the two maternity hospitals than that reported in developed countries or even in developing countries. A study conducted in Australia and New Zealand found an annual average of 1.3% of ICU admissions (Alkema et al , 2016; Maiden et al , 2020), and the frequency in India was 0.5% (Vargas et al , 2019). The results were also higher than the WHO estimate for pregnant Brazilians requiring ICU admission (2.1%) (Souza et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although obstetric causes are the main reason for MNM admitted to the ICU [42,43], considering the development of reproductive medicine and other related medicine, perinatal complications and comorbidities tend to occur in women with underlying diseases, which make the treatments of indirect obstetric causes too complex and beyond the capacity of obstetricians [44]. The main indirect obstetric cause of MNM admitted to the ICU was heart-related diseases, while the control group is epilepsy .According to a national research studied in China, the incidence of MMR caused by heart-related diseases rose by 1.5 per 100,000 between 2013 and 2016 [11].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of severe disease, and the rates of mechanical ventilation and mortality are also observed to be higher in Sub-Saharan Africa than in developed countries [1]. As many as 90% of ICU patients in developing countries required mechanical ventilation [10], whereas much lower rates of 19%-45% have been reported in high-income countries such as Netherlands and Australia [11][12][13]. Mortality rates following obstetric ICU admission of 34.8%-49% have been reported in sub-Saharan Africa [2,6,10] compared to 5.1% in China and <1% in Australia and New Zealand [11,14].…”
Section: Plos Onementioning
confidence: 99%
“…As many as 90% of ICU patients in developing countries required mechanical ventilation [10], whereas much lower rates of 19%-45% have been reported in high-income countries such as Netherlands and Australia [11][12][13]. Mortality rates following obstetric ICU admission of 34.8%-49% have been reported in sub-Saharan Africa [2,6,10] compared to 5.1% in China and <1% in Australia and New Zealand [11,14]. A mean duration of stay of 3-4 days has been reported in Asia and Europe [12,15] and hypertensive disorders of pregnancy (HDP), hemorrhage, and sepsis are often the main indications for ICU admission [1,2,6].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation